The Influence of Biospheric Values and Green Advertising on Green Product Purchase Intention with Green Product Values as Intervening - Wiratama, Raihan; Sugandini, Dyah (Southeast Asian Business Review, 2024)
This research discusses the influence of Biospheric Values and Green Advertising on Green Product Purchase Intention, with Green Product Values as an intervening variable. Data for this research were collected using a quantitative approach with a questionnaire method. The data used were primary data from the responses of 110 residents in the Special Region of Yogyakarta selected through purposive sampling. Data collection was measured using a Likert scale and then analyzed using PLS in SMART PLS 3.0 software. The results of the study indicate that 1) Biospheric Values directly and significantly influence Green Product Purchase Intention, 2) Green Advertising directly and significantly influences Green Product Purchase Intention, 3) Green Product Values can act as an intervening variable in the positive and significant influence of Biospheric Values on Green Product Purchase Intention, 4) Green Product Values can act as an intervening variable in the positive and significant influence of Green Advertising on Green Product Purchase Intention.